THE USE OF SONG MEDIA TO INCREASE STUDENT PARTICIPATION IN ENGLISH GRAMMAR LEARNING ON CLASS XI STUDENTS OF SMK NEGERI 4 LAHAT DEPARTMENT OF ACCOUNTING FOR THE ACADEMIC YEAR OF 2019/2020 - Afrida (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2021)
Student participation is an important aspect in learning, including learning English grammar. This study is intended to overcome the problem of student participation in learning English grammar by using the media song. With tone, authenticity and lyrics, the song gives the effect of feeling happy, motivated, as well as an example of language grammar in use. The research was conducted in class XI in accounting department of SMK Negeri 4 Lahat. Data were collected through observations, questionnaires, and tests/tests. Based on initial observations, a number of obstacles were identified, among which students looked passive and paid less attention to learning English grammar. The research team agrees that the core of the problem is learning which tends to be deductive in nature, that is, students are not given enough real examples. Otherwise, teachers only give students more with formulas. The research team reached an agreement on how to overcome the problem, namely by implementing English grammar learning using song media. At the first meeting, there was progress on what the CAR team was concerned about. Although there are still shortcomings, teacher performance is improving. In general, student participation also increased, except for a few aspects such as the absence of questions asked by students. However, the progress achieved in the first meeting can be maintained at the second meeting. Some advances tend to increase in intensity. The results of the pre-post-test of the second meeting even increased quite sharply. Overall evaluation at the end of the cycle, including taking into account student responses through questionnaires, shows the success of CAR.